The End of History? - Jean-Marc Chadelat (Sillages Critiques)
The conclusive play of Shakespeare’s English historical sequence ends with the prediction of a revelation of concealed truths and unending peace and plenty. Yet the apocalypse proclaimed by the archbishop of Canterbury in Henry VIII depends on a secular teleology of time highlighting its problematic ambivalence. In all these plays, a persistent expectation is aroused by the notion that English history is directed towards the completion of a process and the revelation of a purpose. Furthermore, the discrepancy between the chronological order of kings and the successive composition of plays suggests a form of determinism at work in history. The assertion of free will articulated by several characters is more often than not belied by the retrospective awareness that human agency was instrumental in achieving a design beyond human control and intelligence. The spectators however are denied access to a genuine apocalypse and a sense of closure. The unsettling end of the sequence of plays is deceptively restorative and Henry VIII, unlike the Book of Revelations, leaves the final outcome of events open. As a result of this inconclusive ending, the indefinitely postponed realization of the prophecy of an imminent end of history and attendant revelation of hidden things is simultaneously endowed with a futuristic and symbolic meaning.